IT BASED ENGLISH TRAINING FOR EARLY CHILDHOOD EDUCATION TEACHERS IN BUNTU PANE - Iin Almeina Lubis; Febby Madonna Yuma; Guntur Maha Putra (STMIK Royal, 2020)
Abstract: The aim of this Community Service is to provide IT-based English language learning media training using Microsoft PowerPoint and make simple videos. This dedication was given to Early Childhood Education Teachers in the Buntu Pane District. The dedication session consisted of distributing material to participants, stages of making Microsoft PowerPoint, and making simple videos. The model used is the training model, delivering material, question and answer session, and direct practice. In general, participants claimed that the training schedule was appropriate, time was shared (delivering material, demonstrations, questions and answers, and direct practice). The participants of the activity were satisfied with the topic presented and felt that most of the expectations and objectives of the service had been fulfilled. The evaluation results showed that the material presented could be well followed. Keywords: english language; microsoft powerpoint; early childhood education teachers Abstrak: Tujuan dari Pengabdian Masyarakat ini adalah memberikan pelatihan media pembelajaran bahasa inggris berbasis IT menggunakan Mcrosoft PowerPoint dan membuat video sederhana. Pengabdian ini diberikan kepada Guru Guru PAUD ( Pendidikan Anak Usia Dini ) Se-Kecamatan Buntu Pane. Sesi Pengabdian terdiri dari membagikan materi kepada peserta, tahapan-tahapan membuat Microsoft PowerPoint, dan membuat video sederhana. Model yang digunakan adalah model pelatihan, menyampaikan materi, sesi tanya jawab, dan praktek langsung. Secara umum, peserta mengklaim bahwa jadwal pelatihan sudah tepat, pembagian waktu ( menyampaikan materi, demonstrasi, tanya jawab, dan praktek langsung). Peserta kegiatan puas dengan topik yang disajikan dan merasa bahwa sebagian besar harapan dan tujuan pengabdian sudah terpenuhi. Hasil evaluasi menunjukkan bahwa materi yang disampaikan dapat diikuti dengan baik. Kata kunci: bahasa inggris; microsoft powerpoint; guru pendidikan anak usia dini (PAUD)